Latent tuberculosis infection in the Polish prison staff - Aneta Filipek-Czerska; Jan Kazimierz Karczewski; Iwona Gładysz (Nofer Institute of Occupational Medicine, 2021)
Background Tuberculosis is a chronic infectious disease caused by acid-fast mycobacteria from the Mycobacterium tuberculosis complex group. The disease spreads when people with pulmonary tuberculosis excrete bacteria when they cough, sneeze, laugh or speak. Prisons are often called reservoirs of patients with tuberculosis, posing a great threat to their staff. Longer working hours in prison and penitentiary facilities aid latent contamination among the prison staff. So far, there have been few works discussing latent tuberculosis infection issues among the prisoners and prison staff. Material and Methods A total of 84 employees of penitentiary facilities located in the Lublin Voivodship were examined using the QuantiFERON-TB Gold In-Tube (QFT-GIT) test which was approved for use in 2005 by the U.S. Food and Drug Administration as an aid in the diagnosis of Mycobacterium tuberculosis . The material for the research included blood samples collected using the QFT-GIT. Results Positive test results of latent tuberculosis infections were found in 16.6% of officers. The highest percentage with positive results of tuberculosis infections was found among the surveyed single women aged 36-57, working in penitentiary facilities. There have been no statistically significant differences between the position of officers and the risk factors increasing the chance of the latent tuberculosis infection. Work experience and contact with inmates were found to have an impact on tuberculosis infection. Conclusions The obtained results partially confirm other authors' observations concerning the influence of the risk factors of latent tuberculosis infections in prisons. Work experience and contact with inmates have an impact on tuberculosis infections among the prison staff in the Lublin Voivodeship. Med Pr. 2021;72(4):415-22